Forming Religious Character, Discipline, And Responsibility Through The Habit of “Asnawi Tahluq” - Sukarman, Sukarman; Istiqomah, Dewi Qodar; Embong, Rahimah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2024)
AbstractGlobalization has had a significant impact on education, creating competition and positive achievement, but also causing counter-social behavior. In the context of Islamic education, the formation of spiritual intelligence becomes very important. This research aims to describe the implementation of the Asnawi tahluq habit and the supporting and inhibiting factors. This research uses a qualitative method with a field research approach which is based on the philosophy of postpositivism. Data collection techniques involve observation, interviews and documentation at MTs. Matholi'ul Huda Troso. This school implements "asnawi tahluq" habituation activities which involve all members of the school community, including students, teachers and employees. These activities include reading Asma'ul Husna, sholawat nariyah, and Khatmil Qur'an with the aim of increasing understanding of religion, faith and spirituality. This activity is carried out routinely every day, guided by a special coordinator. Sholawat nariyah emphasizes personal involvement in worship, while reading Khatmil Qur'an helps students understand and appreciate the Qur'an. Supporting factors include kutaib books, relationships with Islamic boarding schools, student motivation, and available facilities. However, there are inhibiting factors such as lack of interest and discipline among students, personal problems, and lack of supervision in several classes which affect the success of the asnawi tahluq habit in the madrasah.